(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
In our paper we examine the problem of increasing the effectiveness of training specialists in educational institutions. It is shown that the professional readiness of students as a personal quality and an essential prerequisite for the effective activity of a specialist, the successful performance of their duties, the correct use of knowledge and experience, helps to quickly adapt to working conditions and promotes further professional development.